Pengaruh Mobilisasi dan Fisioterapi Dada Terhadap Kejadian Ventilator Associated Pneumonia di Unit Perawatan Intensif: Effect of Mobilization and Chest Physiotherapy on the Incidence of Ventilator Associated Pneumonia in the Intensive Care Unit - Hendra Hendra; emil Emil Huriani (Fakultas Keperawatan Universitas Andalas, 2011)
Incidence of Ventilator Associated Pneumonia (VAP) in patients who mounted mechanical ventilation in the Intensive Care Room RS. Dr. M. Djamil was increase, in terms of mobilization for the implementation of mobilization (ambulation) and chest physiotherapy have been prepared in accordance with standard operational procedure (SOP). Presumably this is caused by not all of the implementation of measures given to patients in accordance with SOP. The purpose of this study was to investigate the effect of mobilization (ambulation) and chest physiotherapy on the incidence of VAP in patients who mounted ventilator in intensive care hospital. Dr. M. Djamil Padang. This Quasy- experimental study used static group comparison design, with the number of respondents as many as 20 people. Data analysis was conducted using the Mann-Whitney test. The results showed decreased incidence of VAP in the experimental group, but no significant differences between the experimental group and control group with p-value = 0189. Need to increase the implementation of mobilization (ambulation) and chest physiotherapy on patients who mounted ventilators to prevent Ventilator Associated Pneumonia (VAP).